Pengaruh zonasi dalam kandang closed house terhadap kadar amonia dan dampaknya pada kualitas daging broiler di musim penghujan - Renata Renata; Teysar Adi Sarjana; Sri Kismiati (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2018)
This experiment was conducted to determine the effect of zonation in closed house on ammonia levels and its impact on broiler chicken quality in the rainy season. The research was held in closed house, Faculty of Animal Husbandry and Agriculture, Diponegoro University. Three hundred and sixty broilers were divided into 24 groups (4 treatment, 6 placement groups of broiler): T1 (Zone 1, at the inlet position of the cage), T2 (Zone 2; ¼ of the length of the cage), T3 (Zone 3; ½ from the length of the cage ); T4 (Zone 4; ¾ of the length of the cage). During the study of ammonia levels, the temperature, humidity, and wind velocity inside and outside the cage were taken to obtain an overview of several factors that contribute to ammonia levels. The parameters observed were water holding capacity, pH, color, moisture content, fat content, and protein content. Water holding capacity and the color of the upper thigh meat increased significantly in the zone near the outlet (p <0.05), but the water holding capacity and the color of the lower thighs and breast meat did not increase (p> 0.05) in the zone near the outlet, but it has a darker meat color on the zone near the outlet. The pH did not show any significant difference (p> 0.05) in the zone near the outlet. Water content followed by fat content of breast meat showed no significant difference (p> 0.05) due to zoning. Breast protein content significantly increased (p <0.05) in the zone near the outlet. It was concluded that placement in the zone near outlet had impact on the increase of water holding capacity, color, and protein content. Nevertheless, an increase in meat protein in the zone near the outlet is not followed by increased meat protein mass.